Mapping the Discourse of Islamic Epistemology in Addressing Modern Science Crises: A Systematic Literature Review (2020-2025) - Wahyu Sihab; Muhammad Daffa Imaduddin (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
This study examines the epistemological crisis in modern science from an Islamic perspective by employing a Systematic Literature Review (SLR) approach based on the PRISMA framework. The study is motivated by the growing concern that modern scientific paradigms tend to emphasize empirical and instrumental dimensions of knowledge while marginalizing ethical, metaphysical, and spiritual aspects. Data were collected from reputable databases, including Publis or Peris, Web of Science, and Google Scholar, covering publications from 2020 to 2025, resulting in 35 selected articles after a rigorous screening process. The findings reveal four major themes: (1) critiques of dominant scientific paradigms, (2) Islamic epistemology as an integrative framework, (3) epistemological tensions in educational practices, and (4) the broader implications of epistemological imbalance in contemporary life. The study shows that while Islamic epistemology offers a conceptually robust and integrative framework based on revelation, reason, and moral values, its development remains largely normative and lacks operational models in practice. Therefore, this study highlights the need for a more dialogical and integrative approach that bridges modern scientific methodologies with ethical-spiritual dimensions. The findings contribute to the development of a more balanced epistemological framework and provide a foundation for future research, particularly in the context of education and knowledge reconstruction.